THETA AND ALPHA EEG FREQUENCY INTERPLAY IN SUBJECTS WITH MILD COGNITIVE IMPAIRMENT: EVIDENCE FROM EEG, MRI AND SPECT BRAIN MODIFICATIONS - Davide Vito Moretti (Frontiers in Aging Neuroscience, 2015)
Background: reduction of regional cerebral perfusion in hippocampus as well as temporo-parietal and medial temporal cortex atrophy are associated to mild cognitive impairment (MCI) due to Alzheimer disease (AD). Methods: 74 adult subjects with MCI underwent clinical and neuropsychological evaluation, electroencephalogram (EEG) recording and high resolution 3D magnetic resonance imaging (MRI). Among the patients, a subset of 27 subjects underwent also perfusion single-photon emission computed tomography (SPECT) and hippocampal atrophy evaluation. Alpha3/alpha2 power ratio as well as cortical thickness was computed for each subject. Three MCI groups were detected according to increasing tertile values of alpha3/alpha2 power ratio and difference of cortical thickness among the groups estimated. Results: higher alpha3/alpha2 power ratio group had wider cortical thinning than other groups, mapped to the Supramarginal and Precuneus bilaterally. Subjects with higher alpha3/alpha2 frequency power ratio showed a constant trend to a lower perfusion than lower alpha3/alpha2 group. Moreover, this group correlates with both a bigger hippocampal atrophy and an increase of theta frequency power.Conclusion: Higher EEG alpha3/alpha2 power ratio was associated with temporo-parietal cortical thinning, hippocampal atrophy and reduction of regional cerebral perfusion in medial temporal cortex. In this group an increase of theta frequency power was detected inMCI subjects. The combination of higher EEG alpha3/alpha2 power ratio, cortical thickness measure and regional cerebral perfusion reveals a complex interplay between EEG cerebral rhythms, structural and functional brain modifications.